An Analysis of Grammatical Error By Facebook Users: A Study at Students of English Department at Muhammadiyah University of Mataram in Academic Year 2015-2016 - Muhammad Hudri (Muhammadiyah University of Mataram, 2017)
This study entitled An Analysis of Grammatical Errors Based on Facebook User at the Group of English Department Program at Muhammadiyah University of Mataram in the academic year 2015-2016. This research focused on the purpose of investigated kinds of grammatical error made by facebook user. The method used a descriptive qualitative method where the instrument employed to collect the data. The total number involved in the group of English Department UMM were 136 members who are consisted of 10 lectures and 126 students. As a result of this study, the researcher found out four kinds of errors were classified into Omission error, Addition error, Misformation error, and Misordering error. The highest rank of their error was Omission and Misformation error (16,4%), the second rank was Addition error (10,8%), the lowest rank was Misordering error (2,8%). These errors were mostly caused the members did not realize the errors of the language they have made.